2017
DOI: 10.1021/acscatal.6b03535
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Photocatalytic Oxidation of Methane to Methanol through Surface Modification of Beta Zeolites

Abstract: The selective oxidation of methane to methanol is achieved by means of a photocatalytic process. For this purpose, designed Bi- and V-containing beta zeolites prepared by incipient wetness impregnation have been used under different test conditions. While the zeolite proves to be photoactive under UVC irradiation toward the total oxidation process, the formation of V2O5 on the surface is an effective alternative for modifying the acid–base surface properties, thus significantly decreasing the undesired CO2 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 38 publications
0
71
0
1
Order By: Relevance
“…[38] The construction of heterojunctions is also an effective means for improving the photocatalytic efficiency. Murcia-López et al [39] loaded V 2 O 5 and BiVO 4 on an Htype BEA zeolite (HBEA), which increased the specific surface area of the catalyst and led to the production of methanol. Recently, Song et al [40] reported that ZnO loaded with metals (Pt, Pd, Au, or Ag) enables the direct oxidation of methane to methanol and formaldehyde using only molecular oxygen as the oxidant.…”
Section: Selective Oxidation Of Methane Into Alcoholsmentioning
confidence: 99%
“…[38] The construction of heterojunctions is also an effective means for improving the photocatalytic efficiency. Murcia-López et al [39] loaded V 2 O 5 and BiVO 4 on an Htype BEA zeolite (HBEA), which increased the specific surface area of the catalyst and led to the production of methanol. Recently, Song et al [40] reported that ZnO loaded with metals (Pt, Pd, Au, or Ag) enables the direct oxidation of methane to methanol and formaldehyde using only molecular oxygen as the oxidant.…”
Section: Selective Oxidation Of Methane Into Alcoholsmentioning
confidence: 99%
“…Despite such potential, there are few reports of photocatalytic processes for CH4 transformation under ambient conditions and with satisfactory selectivity for methanol production. [34][35][36][37] Herein we report metal oxide species anchored on TiO2 as a photon promoted catalysts for methane conversion to methanol in the presence of H2O2 at room temperature and 1 bar gas pressure. Furthermore, we show that iron oxide species are the most active for this process compared with other noble metals or transition metal clusters.…”
Section: Introductionmentioning
confidence: 99%
“…WO 3 has been a classic material in this field supplying hydroxyl radical (·OH) through H 2 O oxidation to turn methane into methanol 1013 . In addition to WO 3 , bismuth-based compounds such as BiVO 4 and Bi 2 WO 6 have also been estimated 14 , while reports of V containing zeolites have emerged recently about tuning the surface acid−base properties to a better methanol selectivity 15,16 . In these researches, the highest methanol production rate is 67.5 μmol g cat −1 h −1 from WO 3 by using electron scavenger 12 , which is still far from satisfaction.…”
Section: Introductionmentioning
confidence: 99%